(untitled) (Acta Scientiarum. Health Sciences, 2020)
Aquatic environment is widely used for recreational, sporting, and therapeutic activities. However, human motor functional behavior in immersion has not been sufficiently described. Such description is necessary to improve strategies used to perform movements in this environment and to possibly transfer them to land. Our goal is to offer a qualitative description of the aquatic motor behavior. We use action research to observe and describe motor behavior in water, which we systematized using the Aquatic Functional Assessment Scale, effects of water on the immersed body, its relationship with functional movements performed on land, and the International Classification of Functioning, Disability and Health (ICF). The results allowed the systematization of aquatic movements based on unique features of water compared to effects of activities and participation of functional movement, under a biopsychosocial view of ICF. Such systematization of aquatic behaviors enables professionals to increase their strategies and interventions in water, through that understand the complexity of this approach and improve physical and therapeutic interventions that will have an impact on health.